2019
DOI: 10.1128/mcb.00391-18
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Chaperone Heat Shock Protein 70 Controls Liver Cancer Initiation and Progression by Regulating Adaptive DNA Damage and Mitogen-Activated Protein Kinase/Extracellular Signal-Regulated Kinase Signaling Pathways

Abstract: Delineating the mechanisms that drive hepatic injury and hepatocellular carcinoma (HCC) progression is critical for development of novel treatments for recurrent and advanced HCC but also for the development of diagnostic and preventive strategies. Heat shock protein 70 (HSP70) acts in concert with several cochaperones and nucleotide exchange factors and plays an essential role in protein quality control that increases survival by protecting cells against environmental stressors. Specifically, the HSP70-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 126 publications
0
14
0
Order By: Relevance
“…Following exposure to different stressors, HSP70s bind to misfolded proteins and prevent their aggregation. As HSP70 family members and their overexpression have been shown to play an oncogenic role in different cancer types, ( 35,36 ) including HCC, ( 37,38 ) we asked if HSP70 family genes were direct transcriptional targets of TEAD4. Because HSPA6 and HSPA1A were the most up‐regulated genes following TEAD4 overexpression (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following exposure to different stressors, HSP70s bind to misfolded proteins and prevent their aggregation. As HSP70 family members and their overexpression have been shown to play an oncogenic role in different cancer types, ( 35,36 ) including HCC, ( 37,38 ) we asked if HSP70 family genes were direct transcriptional targets of TEAD4. Because HSPA6 and HSPA1A were the most up‐regulated genes following TEAD4 overexpression (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of HSP70 family members has been shown to play an oncogenic role in different cancer types, ( 35,36 ) including HCC. ( 37,38 ) In HCC, HSP70 has been reported to drive cell migration, ( 52 ) and genetic ablation of HSP70 was able to markedly impair chemically induced liver tumorigenesis and tumor progression. ( 38 ) Notably, HSP70 is a clinically important marker in HCC diagnosis; HSP70 expression, together with that of glutamine synthetase and glypican 3, is commonly used to differentiate early and low‐grade tumors from dysplastic nodules.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 In addition, the above-mentioned factors further support the survival of malignant liver cells through activation of anti-apoptotic pathways and suppression of immune surveillance. 5,6 It is well documented that in premalignant livers, chronic activation of inflammatory signaling pathways is tightly associated with oxidative/nitrosative stress and generation of reactive oxygen and nitrogen species (ROS and RNS, respectively), 8,9 while carbonyl stress, induced by reactive carbonyl species (RCS), and in particular, α-dicarbonyls (α-dC) has received less attention. Endogenous RCS including acyclic dicarbonyls, methylglyoxal (MGO), and glyoxal are mostly derived from carbohydrate 10 ( Supplementary Fig.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis was generally refuted (6), which led to the idea of direct involvement of Hsp70 in signaling pathways that control major stages of cancer development, including initiation, progression and metastasis. Indeed, several publications demonstrated that knockout of Hsp70 leads to suppression of cancer development at various stages (depending on the cancer model) and these effects correlated with suppression of many signaling pathways involved in cancer development (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%